1971
DOI: 10.1021/ja00732a030
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of unsaturated ketones in solutions. XXVII. Synthesis and photochemistry of .DELTA.1-4-alkyltestosterones

Abstract: The identity of 21 from this reaction with an authentic sample was confirmed by comparison of the infrared spectra and melting points.Fluorescence Spectrum of 14a. The emission from a diethyl ether solution, 1.5 X 10~1 2345 M in 14a, was measured with a Cary Model 15 spectrophotometer equipped with a high-powered mercury-Xenon arc lamp and a monochromator adjusted to provide excitation light at 302 nm. A quartz cell was employed, and excitation was perpendicular to the path of the visible light detector of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The reaction occurs with a low to moderate quantum yield and is somewhat more efficient in 2-propanol, possibly due to the increased energy of the nπ* triplet. With simpler cyclohexadienone models quantum yields are larger than observed here (0.75 to 1),14a and this holds also for the strictly related Δ 1 -dehydrotestosterone, where the rearrangement quantum yield is 0.58, though the value is lower with some 4-alkyl derivatives 14b. Thus, the low Φ r with the present steroidal ketones is probably linked to the fluorine substitution.…”
Section: Discussionsupporting
confidence: 46%
“…The reaction occurs with a low to moderate quantum yield and is somewhat more efficient in 2-propanol, possibly due to the increased energy of the nπ* triplet. With simpler cyclohexadienone models quantum yields are larger than observed here (0.75 to 1),14a and this holds also for the strictly related Δ 1 -dehydrotestosterone, where the rearrangement quantum yield is 0.58, though the value is lower with some 4-alkyl derivatives 14b. Thus, the low Φ r with the present steroidal ketones is probably linked to the fluorine substitution.…”
Section: Discussionsupporting
confidence: 46%
“…On monocyclic cyclohexa-2,5-dienones, it occurs with quantum yields close to unitary (0.75−1), although it has been reported that some substituents affect the efficiency of the photoprocess, a fact mainly attributed to a change in the stability of the suggested zwitterionic intermediates of the rearrangement. In polycyclic derivatives, and in particular with steroid cyclohexadienones, the quantum yield is slightly lower. A value of 0.58 has been reported for Δ 1 -dehydrotestosterone, a compound strictly related to the presently studied ketones.…”
Section: Discussionmentioning
confidence: 75%
“…[8][9][10] In polycyclic derivatives, and in particular with steroid cyclohexadienones, the quantum yield is slightly lower. A value of 0.58 has been reported for ∆ 1 -dehydrotestosterone, 11 a compound strictly related to the presently studied ketones.…”
Section: Discussionmentioning
confidence: 75%
“…The research in our group in the mid- to late 1960s focused on various aspects of ketone photochemistry, including studies which probed the effect of structure on photochemical behavior of cyclohexadienones ring-fused cyclohexenones, and other systems. We used Hammond’s techniques more and more to determine which photochemical reactions involved singlet excited states and which involved triplet excited states. , Using triplet counting techniques based on precisely executed quenching studies, we were finally able to demonstrate convincingly that the rearrangements of α-santonin and other 2,5-cyclohexadienones occur via short-lived triplet excited states with lifetimes in the nanosecond time domain …”
Section: Early Years At Nyu: 1961–1968mentioning
confidence: 99%